Case Report: Preserved umbilical cords underscore family histories of inborn errors of immunity - Nishimura, Madoka; Tomomasa, Dan; Suzuki, Rika; Miyaoka, Futaba; Kanegane, Hirokazu (Frontiers in Immunology, 2025)
A history of susceptibility to infections and a family history of death because of unexplained infections during infancy are helpful in diagnosing inborn errors of immunity (IEIs). However, infections can occur because of various reasons, and determining whether the underlying disease is undoubtedly an IEI is implausible at present. In Japan, preservation of the umbilical cord at birth is customary. Two patients were suspected of having X-linked agammaglobulinemia (XLA); the patients were ultimately diagnosed with XLA based on the history of susceptibility to infections and family histories of deaths of maternal uncles because of infections during infancy. DNA was extracted from umbilical cords that had been preserved for approximately 50 years. The affected children harbored the same Bruton tyrosine kinase (BTK) variants as those detected using the umbilical cord samples of their maternal uncles. Analysis of preserved umbilical cords can help in ascertaining a family history of IEIs.